2017
DOI: 10.1128/jvi.00634-17
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cross-Clade Characterization of Antibody-Mediated Recognition, Complement-Mediated Lysis, and Cell-Mediated Cytotoxicity of HIV-1 Envelope-Specific Antibodies toward Eradication of the HIV-1 Reservoir

Abstract: Immunotherapy with passive administration of broadly neutralizing HIV-1 envelope-specific antibodies (bnAbs) in the setting of established infection in vivo has yielded mixed results. The contribution of different antibodies toward the direct elimination of infected cells is poorly understood. In this study, we determined the ability of 12 well-characterized anti-HIV-1 neutralizing antibodies to recognize and eliminate primary CD4 T cells infected with HIV-1 belonging to clades A, B, C, and D, via antibody-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…Cells that have captured viral material [42,43], or at an early stage of infection, have been proposed to be the main target of CDC [35]. Anti-V1/V2 glycans [35] and anti-V3 antibodies [36,44] were suggested to be better CDC inducers than other antibodies. Yet, the impact of the most recent bNAbs on the complement pathway has not been thoroughly analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Cells that have captured viral material [42,43], or at an early stage of infection, have been proposed to be the main target of CDC [35]. Anti-V1/V2 glycans [35] and anti-V3 antibodies [36,44] were suggested to be better CDC inducers than other antibodies. Yet, the impact of the most recent bNAbs on the complement pathway has not been thoroughly analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity for antibody binding to infected CD4 T cells varies among the bnMAbs. In vitro experiments performed by Mujib et al and others have shown low levels of infected cell binding and ADCC for CD4 binding site antibodies, including VRC01 and 3BNC117 [ 10 , 36 ]. The clearance of infected cells by antibody requires the expression of envelope on the cell surface; however, only a small fraction of HIV-infected cells in blood express unspliced HIV-1 RNA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that defective proviruses may be preferentially targeted by CTLs, perhaps due to mutations or deletions in the HIV-1 nef gene (Bruner et al 2016), whose protein product downregulates MHC-I (Huang et al 2018). If so, pharmacologic blockade of Nef may improve CTL killing of cells harboring intact proviruses and therefore reduce the reservoir (Mujib et al 2017a). …”
Section: Directing the Immune Response To Effectively Target The Resementioning
confidence: 99%